Abdominal drawing-in maneuver is less effective for core stability during high load tasks: a systematic review - Aragón Salamanca, J., C. (Asian Journal of Sports Medicine, 2024)
Context:The abdominal drawing-in maneuver (ADIM) is a technique commonly used to activate deep core muscles for the prevention and rehabilitation of low back pain. However, its benefits during high-load tasks (HLT) are unclear.